Time Domain Reflectometry Computational Technique Using Agilent Vee - Mohamed Dan, Nur Sharizan (2007)
This thesis describes the time domain reflectometry computational technique to locate discontinuities in transmission line using Agilent VEE version 6. The reflection coefficient measurement data were transformed from frequency domain into time domain using Fast Fourier Transform (FFT) technique. Measurements were done on waveguides and coaxial cable using HP 8720B network analyzer. The vector network analyzer (VNA) has a time domain capability where transformation from frequency to time domain data is realized using chirp z-transform (CZT) which can be utilized to locate short circuit discontinuities. Unfortunately, the VNA is heavy, bulky and an expensive way of simulating time domain reflectometry measurement. The frequency-to-time measurement option is not a readily built in feature but needs to be purchased before it is included in the VNA in which it comes at a higher cost for end user. Additionally, frequency-to-time measurement option of the VNA has limited capability with only selected transformation algorithm, window and gating method. This motivates the transformation using computer software instead of VNA to transform data, thus, the development of transformation software. All the measurements and calculations were implemented using transformation software developed using Agilent VEE version 6. The analysis on resolution was done and parameters that affects the resolution; number of points and frequency range, was analyzed. The transformation software transforms frequency domain data to time domain. The peaks in the measurement data represent discontinuity in the test components/devices. Measurements were done on combinations of well define components which includes WR-90 waveguides and RG402 coaxial cable. The performance of the transformation software was tested by comparing the results with true physical measurement of the devices. The results show that the reflection coefficient obtained from the software is in good agreement with the VNA in terms of the location of discontinuity with both VNA and transformation software having ≈5% deviation with the true physical value. The transformation software results are as reliable as the VNA. This transformation software is flexible, cheap and easy to use. It is ready to be incorporated into mobile computer and can be used with any frequency domain measurement device.